Characteristics investigation of composite electrochromic films based on Ni(Oh)2, polyvinyl alcohol, and polyvinylpyrrolidone - Kotok, Valerii; Kovalenko, Vadym; Mikolasek, Miroslav; Ondrejka, Peter; Zima, Oleksandra; Anataichuk, Inna; Vodopyan, Dmitriy; Sukhyy, Kostyantyn (Eastern-European Journal of Enterprise Technologies, 2022)
The cost of electrochromic “smart” windows ranges from 200–800 USD/m2. The high cost is determined by the small volume of production and the high cost of vacuum methods for applying device layers. The development of other methods could lead to lower costs and further mass use of “smart” windows. The paper presents the work on improving the electrochemical method of deposition of electrochromic films based on Ni(OH)2. Composite electrochromic films were deposited from Ni(NO3)2 solutions with the addition of water-soluble polymers – polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and mixtures thereof. Two PVA grades and one PVP grade were used in the experiments. As a result, six films were obtained from solutions of different compositions and concentrations of polymers. An investigation of the optical properties of the films in the initial state showed that there is no intense absorption of light in the entire visible spectrum and the transmission corresponds to a glass substrate. Thus, the formed electrochromic films will not produce tints and visible light absorption in the finished electrochromic element. The electrochemical and electrochromic characteristics of the films differed significantly depending on the amount and specific polymers used. The film obtained from a solution containing PVA grade 24-99 was the most electrochemically active, while the best electrochromic characteristics were in the film deposited from a solution of a mixture of PVP grade 24-99 and PVP. Moreover, the films obtained in solutions containing separately PVA grade 24-99 and PVP had worse electrochromic characteristics, and the electrochemical characteristics were the same or worse relative to the film obtained in a mixture of polymers. The results of the method of electrochemical impedance spectroscopy showed compliance with the found electrochromic and electrochemical characteristics of the formed films.